Iron scavenging and suppression of collagen cross-linking underlie antifibrotic effects of carnosine in the heart with obesity - Berdaweel, Islam A.; Monroe, T. Blake; Alowaisi, Amany A.; Mahoney, Jolonda C.; Liang, I-Chau; Berns, Kaitlyn A.; Gao, Dylan; McLendon, Jared M.; Anderson, Ethan J. (Frontiers in Pharmacology, 2024)
Oral consumption of histidyl dipeptides such as l-carnosine has been suggested to promote cardiometabolic health, although therapeutic mechanisms remain incompletely understood. We recently reported that oral consumption of a carnosine analog suppressed markers of fibrosis in liver of obese mice, but whether antifibrotic effects of carnosine extend to the heart is not known, nor are the mechanisms by which carnosine is acting. Here, we investigated whether oral carnosine was able to mitigate the adverse cardiac remodeling associated with diet induced obesity in a mouse model of enhanced lipid peroxidation (i.e., glutathione peroxidase 4 deficient mice, GPx4+/−), a model which mimics many of the pathophysiological aspects of metabolic syndrome and T2 diabetes in humans. Wild-type (WT) and GPx4+/−male mice were randomly fed a standard (CNTL) or high fat high sucrose diet (HFHS) for 16 weeks. Seven weeks after starting the diet, a subset of the HFHS mice received carnosine (80 mM) in their drinking water for duration of the study. Carnosine treatment led to a moderate improvement in glycemic control in WT and GPx4+/−mice on HFHS diet, although insulin sensitivity was not significantly affected. Interestingly, while our transcriptomic analysis revealed that carnosine therapy had only modest impact on global gene expression in the heart, carnosine substantially upregulated cardiac GPx4 expression in both WT and GPx4+/−mice on HFHS diet. Carnosine also significantly reduced protein carbonyls and iron levels in myocardial tissue from both genotypes on HFHS diet. Importantly, we observed a robust antifibrotic effect of carnosine therapy in hearts from mice on HFHS diet, which further in vitro experiments suggest is due to carnosine’s ability to suppress collagen-cross-linking. Collectively, this study reveals antifibrotic potential of carnosine in the heart with obesity and illustrates key mechanisms by which it may be acting.